1984
DOI: 10.1207/s15327752jpa4804_14
|View full text |Cite
|
Sign up to set email alerts
|

Locus of Control in Children of Divorce

Abstract: Scores on the Nowicki-Strickland Locus of Control Scale for Children (N-SLOCSC) were compared for third and fifth grade boys and girls from intact versus maritally disrupted family backgrounds. Significant main effects for each independent variable revealed that fifth graders more than third, boys more than girls, and the marital disruption more than the intact group, exhibited higher internality in their locus of control scores. These findings strongly suggest that experiencing a parental divorce in childhood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
1

Year Published

1991
1991
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 2 publications
2
8
1
Order By: Relevance
“…These finding are contrary to previous research which indicates that family structure and socioeconomic status each have a positive relationship with self-efficacy (Gecas and Schwalbe 1983;Kalter et al 1984), with greater self-efficacy associated with married, higher SES families. These results are perhaps explained by the unique student population making up the current Note: N = 165-190. β 1 is for variable at entry; β 2 is for variable in the full model † p < .10, * p < .05, * * p < .01, * * * p < .001…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…These finding are contrary to previous research which indicates that family structure and socioeconomic status each have a positive relationship with self-efficacy (Gecas and Schwalbe 1983;Kalter et al 1984), with greater self-efficacy associated with married, higher SES families. These results are perhaps explained by the unique student population making up the current Note: N = 165-190. β 1 is for variable at entry; β 2 is for variable in the full model † p < .10, * p < .05, * * p < .01, * * * p < .001…”
Section: Discussioncontrasting
confidence: 99%
“…Individuals from intact homes reported higher levels of self-efficacy compared to children from single-parent homes (Kalter et al 1984;Kurtz and Derevensky 1993;Long et al 1987). Socioeconomic status also relates to efficacy beliefs, with individuals raised in lower socioeconomic homes reporting lower levels of self-efficacy (Coleman and Karraker 1997;Gecas and Schwalbe 1983;Lin 2003).…”
Section: Family Background and Self-efficacy Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Criminal behavior, violence and impairment of masculine development: In their paper, Kalter et al [25], described a clinical study, carried out during a period of 10 years, with approximately 600 children of divorced parents. It was found that boys to divorced parents, who remained in the custody of their mother, had impaired masculine development, due to lack of a male figure.…”
Section: Behavioral Problems and Depressionmentioning
confidence: 99%